Bridging Theoretical Foundations with Practical Applications in Nonlinear Analysis and Optimization - Chinnakaran, Anand (Journal of Educational Research and Policies, 2025)
Z. Mustafa [8] introduced generalized metric space called b2-metric space. Kamran et al. [7], have dealt with an extended b- metric space. The aim of this paper is to establish a notion of a generalized extended b2 metric space which extends and generalizes metric space due to Z. Mustafa [8], Khan et al [10] and Kamran et al. [7]. Also we prove a fixed point theorem on a generalized extended b2 metric space.